Let's tackle each question step by step.
Question 1
Given Quadratic Equation: \[ -2x^2 - 3x + 2 = 0\]
We will test the given values (you didn't specify which values to test, so you will need to input the values you're given). Let's assume we test with \( x = -2, -1, 0, 1, 2 \).
-
If \( x = -2 \): \[ -2(-2)^2 - 3(-2) + 2 = -2(4) + 6 + 2 = -8 + 6 + 2 = 0
\text{ (solution)} \] -
If \( x = -1 \): \[ -2(-1)^2 - 3(-1) + 2 = -2(1) + 3 + 2 = -2 + 3 + 2 = 3
\text{ (not a solution)} \] -
If \( x = 0 \): \[ -2(0)^2 - 3(0) + 2 = 0 + 0 + 2 = 2
\text{ (not a solution)} \] -
If \( x = 1 \): \[ -2(1)^2 - 3(1) + 2 = -2 - 3 + 2 = -3
\text{ (not a solution)} \] -
If \( x = 2 \): \[ -2(2)^2 - 3(2) + 2 = -2(4) - 6 + 2 = -8 - 6 + 2 = -12
\text{ (not a solution)} \]
The solution set from this example:
- Only \( x = -2 \) is in the solution set.
Question 2
Solve: \[ x^2 = 289\]
Taking the square root on both sides: \[ x = \sqrt{289} \quad \text{or} \quad x = -\sqrt{289} \] Thus, the solutions are: \[ x = 17 \quad \text{and} \quad x = -17 \]
The lesser number first: \[ {-17, 17} \]
Question 3
Given Quadratic Equation: \[ -9 + (x - 3)^2 - 4 = -4\]
First, simplify the equation: \[ -9 + (x - 3)^2 - 4 + 4 = 0 \] So we have: \[ -9 + (x - 3)^2 = 0 \] This simplifies to: \[ (x - 3)^2 = 9 \]
Now, take the square root of both sides: \[ x - 3 = 3 \quad \text{or} \quad x - 3 = -3 \] Solving these gives:
- \(x - 3 = 3 \) ⇒ \( x = 6\)
- \( x - 3 = -3 \) ⇒ \( x = 0\)
The values that are in the solution set from given options are:
- 8 (not in the set)
- 2 (not in the set)
- 16 (not in the set)
- -2 (not in the set)
- 28 (not in the set)
- -10 (not in the set)
So the values 0 and 6 would be in the solution set if included.
Final Responses:
- For Question 1: Only \( x = -2 \) is in the solution set.
- For Question 2: \( {-17, 17} \).
- For Question 3: \( x = 0 \) and \( x = 6\).